Enhancing professional development in digital STEM education: cross-disciplinary success factors and barriers - Lüsse, Mientje; Sowinski, Ronja; Stamer, Larissa-Marie; Abels, Simone; Brückmann, Maja (Frontiers in Psychology, 2025)
The increasing integration of digital tools into teaching presents opportunities to enhance interactivity, flexibility, and student-centeredness for science education. However, for these opportunities to be fully realized, teachers need to develop the necessary competencies and positive beliefs to effectively incorporate digital media into their pedagogical practices. Therefore, offering high-quality professional development (PD) is essential. Such programs provide teachers with hands-on training, strengthen their self-efficacy, and support student-centered teaching strategies, including the reflective use of digital media. Our ministry-funded project LFB-Labs-digital has developed empirically based PD programs in student labs across different subjects. For this context, a design-based research (DBR) approach was conducted within an interdisciplinary quality management (QM) to aim at analyzing specific success factors and barriers of these PD programs. Hereby, we collect data from regular web-based discussions and short follow-up interviews with PD facilitators about their PD programs as well as incorporated observations. The evaluation framework was aligned with established criteria for effective PD, allowing for a systematic analysis of key success factors and necessary modifications. Our findings highlight several key factors for the success of PD programs in student labs. Identified success factors including technical support, curricular alignment, flexible formats, hands-on orientation, peer support and structured reflection opportunities that help teachers critically evaluate and adapt digital strategies to their teaching practice. These factors must be balanced against persistent barriers such as technical and organizational barriers as well as teachers’ heterogeneous digital competencies. Facilitators emphasize the need for PD programs that address diverse teacher needs while maintaining coherence in content delivery. By integrating multiple perspectives—facilitators, and systematic observations—this study contributes to a deeper understanding of how student labs can function as effective PD environments and provides concrete insights for scaling up and optimizing digital competency acquisition across subjects.